Minimally Invasive Lumbar Decompression (MILD) in Patients with Lumbar Spinal Stenosis: A Systematic Review of Randomized and Prospective Trials - Orhurhu V; Brancolini S; Zheng D; Snyder S; Jevotovsky DS; Chopra H; Sahni S; Li N; D’Souza RS; Evankovich M; Lynch B; Farrell ME; et al. (Journal of Pain Research)
Vwaire Orhurhu,1 Scott Brancolini,1 Danielle Zheng,1 Sean Snyder,1 David S Jevotovsky,2 Harman Chopra,3 Sidharth Sahni,2 Nathan Li,4 Ryan S D’Souza,5 Maria Evankovich,1 Brendan Lynch,1 Michael Edward Farrell,1 Benedict J Alter,1 Trent Emerick1 1Department of Anesthesiology & Perioperative Medicine, Division of Chronic Pain Management, University of Pittsburgh Medical Center, Pittsburgh, PA, USA; 2Department of Rehabilitation Medicine, NYU Langone Health, New York, NY, USA; 3Department of Physical Medicine and Rehabilitation, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 4Department of Orthopedic Surgery, Boston University School of Medicine, Boston, MA, USA; 5Department of Anesthesiology and Perioperative Medicine, Mayo Clinic, Rochester, MN, USACorrespondence: Sidharth Sahni, Email sisahni@gmail.comBackground/Importance: Lumbar spinal stenosis (LSS) remains one of the most common causes of pain and functional disability in patients with chronic pain. Minimally invasive lumbar decompression (MILD) has been shown to reduce pain and improve function with lumbar spinal stenosis. However, very few large studies have evaluated the short- and long-term effects of MILD on functional improvement and pain reduction.Purpose: To evaluate the evidence on the MILD procedure for chronic pain patients with LSS.Methods: A systematic review of randomized and prospective trials investigating the effectiveness of the MILD procedure in managing low back pain and lower extremity pain was performed using PubMed, Medline, Embase, Google Scholar, clinical trial.gov, and Cochrane. We utilized the Cochrane review methodologic quality assessment, GRADE and Interventional Pain Management Techniques – Quality Appraisal of Reliability and Risk of Bias Assessment (IPM-QRB) and IPM-QRB for Nonrandomized Studies (IPM-QRBNR) to guide our data extraction and assessment of study quality methods. Our study summarized and presented the evidence quality on a scale of 1 to 5.Results: Fifteen MILD studies met our inclusion criteria. There were 8 studies that were multicenter prospective trials, and 7 studies were single centers prospective trials. The evidence based on a systematic review of prospective trials investigating the efficacy of the MILD procedure showed a median level 2b evidence with several level 1b studies available. Pain and functional outcome GRADE assessment of studies was high quality.Conclusion: This systematic review suggests that the MILD procedure can be effective in managing chronic pain patients with lumbar spinal stenosis.Keywords: minimally invasive lumbar decompression, MILD, lumbar spinal stenosis, review, pain